2000
DOI: 10.1073/pnas.210394297
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 regulates the location, stability, and transcriptional activity of β-catenin

Abstract: The insulin-like growth factor (IGF) type 1 receptor is required for growth, transformation, and protection from apoptosis. IGFs can enhance cell migration, which is known to be influenced via regulation of the E-cadherin͞␤-catenin complex. We sought to investigate whether IGF-1 modulated the interaction between E-cadherin and ␤-catenin in human colorectal cancer cells. We used the C10 cell line, which we established and have previously shown to lack adenomatous polyposis coli, E-cadherin, or ␤-catenin mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
174
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(183 citation statements)
references
References 62 publications
7
174
0
Order By: Relevance
“…Bcr-Abl can phosphorylate b-catenin, which inhibits its association with Axin/GSK-3b complex and reduces its phosphorylation by GSK-3b and subsequent proteosomal degradation (Coluccia et al, 2007). IGF-1R activation also Autocrine IGF-1 signaling in CML A Lakshmikuttyamma et al leads to b-catenin phosphorylation, stabilization and nuclear localization (Playford et al, 2000;Chen et al, 2005). Thus, IGF-1 signaling may be responsible for b-catenin stability or it may cooperate with Bcr-Abl to further enhance b-catenin stability.…”
Section: Discussionmentioning
confidence: 99%
“…Bcr-Abl can phosphorylate b-catenin, which inhibits its association with Axin/GSK-3b complex and reduces its phosphorylation by GSK-3b and subsequent proteosomal degradation (Coluccia et al, 2007). IGF-1R activation also Autocrine IGF-1 signaling in CML A Lakshmikuttyamma et al leads to b-catenin phosphorylation, stabilization and nuclear localization (Playford et al, 2000;Chen et al, 2005). Thus, IGF-1 signaling may be responsible for b-catenin stability or it may cooperate with Bcr-Abl to further enhance b-catenin stability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to playing a role in cell proliferation (31,32), neuropeptides and other regulatory peptides may have a possible effect on the control of adhesion between neighboring epithelial cells (33) and on catenin regulation, which is a crucial process related to colonic carcinogenesis (34). Interestingly, it has been observed that adherens junctions and tight junctions are regulated by gastrin in epithelial cells, a fact that may contribute to the co-carcinogenic role of this prohormone in colorectal carcinoma (35).…”
Section: Discussionmentioning
confidence: 99%
“…The effect seems to involve the canonical Wnt signaling family because it was accompanied by nuclear accumulation of ␤-catenin ( Figure 4B). Some cases of cross talk between Wnt and insulin pathways have been reported (Fukumoto et al, 2001;Harwood, 2001), including on ␤-catenin activity (Papkoff, 1997;Playford et al, 2000;Desbois-Mouthon et al, 2001). The pool of GSK-3 targeted by Wnt is mostly nonphosphorylated by the insulin/PKB pathway (Ding et al, 2000).…”
Section: Gsk-3 Inhibition Is One Component In the Initiation Of Diffementioning
confidence: 99%